KEPEMILIKAN MANAJERIAL DAN CASH HOLDING PADA PERUSAHAAN KELUARGA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Riyanto, Anis; Venusita, Lintang (Jurnal Akuntansi AKUNESA, 2020)
This research has purpose to prove the effect of managerial ownership on cash holding in family companies. The population and research sample are family firm listed on the Indonesia Stock Exchange during 2014-2017. Based on sample collection techniques Puposive sampling method the number of samples used was 44 samples with a sample unit of 176. The statistical method used is regretion analysis with the help of E-VIEWS 10. The results prove that managerial ownership has annegatif effect of cash holding in family firm on Indonesia Stock Exchange during 2014-2017.The greater managerial ownership will make the company's cash holding decrease because the manager feels that he owns the company and does not want problems related to too much cash holding in the company to appear.